PENGEMBANGAN MODEL PERMAINAN BERBASIS SIRKUIT TERHADAP KEMAMPUAN GERAK DASAR LOKOMOTOR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article examines the effect of the application of circuit-based games on the improvement of basic locomotor movement skills in elementary school students. The study used a quasi experimental design with the One Group Pretest Posttest model. The subject of the study is a fourth grade student of SDN Gampingrowo 2 The instruments used included tests of locomotor motion ability (zig-zag running, obstacle jumping, and long jump without prefix). The results showed a significant improvement in students' locomotor movement ability after circuit game treatment. These findings corroborate that circuit games are an effective, fun, and structured approach to improve basic locomotor movement skills in the context of elementary school PJOK learning.